BRAND EQUITY OF KAPAL API SACHET COFFEE IN SAWANGAN: A COMPREHENSIVE STUDY USING MIXED METHODS - Muhammad Abdullah; Hary Mulyadi; Oby Eko Purwanto; Ati Chandrasari; Valentine Theresia Simamora (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
Indonesia, as one of the largest coffee producers in the world, has a promising market for sachet coffee products, with Kapal Api being one of the most popular brands. This study aims to measure Kapal Api’s brand equity through four main aspects: brand awareness, brand association, brand perceived quality, and brand loyalty. The research method employed mixed methods, using qualitative analysis through focus group discussions to explore brand awareness, brand perceived quality, and brand loyalty, and quantitative analysis to test the brand association hypothesis using the Cochran test. The study involved 96 respondents in Sawangan selected through purposive sampling, aged at least 17 years, residing in Sawangan, and actively consuming sachet coffee within the last month. The results showed that 100% of respondents recognized Kapal Api as a leading sachet coffee brand and it became the top of mind in Sawangan. Kapal Api’s brand association was generally rated positively, especially regarding its distinctive taste and aroma. The price was considered fair in relation to the quality and flavor offered. The product is easy to brew and suitable for consumption in various situations such as in the morning, while working, or relaxing. Most respondents rated Kapal Api as having good quality, characterized by a strong and consistent taste and aroma, product durability during storage, and attractive packaging. Kapal Api’s brand loyalty was strong, demonstrated by an inverted loyalty pyramid with the highest percentage of committed buyers, indicating a very good level of loyalty.